Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Memilih Maxim Sebagai Media Tranportasi Online di Kota Kupang - Yehugen, Aleksander Serapion; Fangidae, Yosefa Silina; Banfatin, Blasius Noven Robinson; Lian, Yohanes Pemandi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to identify and analyze the factors that influence consumer decisions in choosing Maxim as an on line transportation service provider in Kupang City. The method used was qualitative with a phenomenological approach, and information was collected through interviews and online questionnaires from a hundred respondents consisting of students (63%), employees (20%), and the general public (17%). The results showed that the main source of information regarding the use of Maxim came from word of mouth (50%) and social media (41%). Most users (61%) have been using the service for less than a year, with an average frequency of use of 3 times a week. Factors that influence consumer decisions include competitive pricing, good customer service, and features that allow cost estimates and arrival times. However, the accuracy of the map in the app is one that needs improvement. The conclusion of this study shows that Maxim has successfully met consumer expectations, but further improvements are needed, particularly on the navigation system, to increase customer satisfaction and loyalty in Kupang City.